International workshop on smalltalk technologies 2011 special issue. (27th December 2012) - Plantec, A.; Lagadec, L.; Plantec, A.; Lagadec, L.
SUMMARY Smalltalk is an exciting object‐oriented language in which even primitive values are uniformly handled as normal objects described by classes that one can browse and extend. Smalltalk was born during the seventies, but the ideas behind currently available implementations are still modern and innovative. Smalltalk benefits from being a highly expressive language in which complex and powerful systems can emerge from the composition of simple building blocks. Thanks to its dynamic nature, fast prototyping and agile software development are made possible. Smalltalk also benefits from having powerful meta‐programming facilities. A program is able to query and to change its own structure and behavior. Smalltalk is not only a language but also an interactive system that is implemented in Smalltalk and that can be customized according to users needs. This special issue presents four extended versions of research papers from the third International Workshop on Smalltalk Technologies (IWST) that was organized at Edinburgh on September 2011. Johan Fabry et al. 1 presented Phantom, an aspect language that includes recent research results in aspect interactions and reentrancy control. Phantom is designed to be optimized and compiled where possible. Increasing use of reflection and meta‐programming techniques in real world applications underlines the need for more dynamic approaches. New approaches have shifted to object‐specific reuse. Jorge Ressia et al. 2 proposed a new abstraction called a talent, which models features that are shared between objects of different class hierarchies. Martin Dias et al. 3 presented Fuel, a general‐purpose object serializer that focuses on speed, through a compact binary format and an efficient pickling algorithm. Fuel serializes any object, thus having a full‐featured language‐specific format. Redesign of nontrivial software is often a challenge. Ciprian Teodorov et al. 4 addressed physical‐design automation and presented a methodological approach relying on model‐driven engineering. Also, they summarized some lessons learned from the incremental redesign of Madeo, a toolkit that targets field‐programmable gate array design automation. The goal of the IWST workshop series is to create and foster a forum around advances or experiences in Smalltalk. Each IWST workshop is organized as a collocated event of the European Smalltalk User Group annual conference. Copyright © 2012 John Wiley & Sons, Ltd.